2019
DOI: 10.1101/558957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient developmental increase of prefrontal activity alters network maturation and causes cognitive dysfunction in adult mice

Abstract: Disturbed neuronal activity in neuropsychiatric pathologies emerges during development and might cause multifold neuronal dysfunction by interfering with apoptosis, dendritic growth and synapse formation. However, how altered electrical activity early in life impacts neuronal function and behavior of adults is unknown. Here, we address this question by transiently increasing the coordinated activity of layer 2/3 pyramidal neurons in the medial prefrontal cortex of neonatal mice and monitoring long-term functio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…If reduced early PYRs II/III activity is deleterious, the opposite effect is equally detrimental. Unpublished results from our group suggest, for instance, that a protracted but subtle increase of PYRs II/III firing across the first two postnatal weeks results in long-term prefrontal microcircuit disruption and an excitation/inhibition (E/I) imbalance that worsens over time, equally leading to cognitive and social deficits [43]. Similar deficits have also been described in mouse models of autism spectrum disorder, which are characterized by increased prefrontal activity [54][55][56].…”
Section: Figure 2 Schematic Representation Of the Development Of Beta-gamma Prefrontal Oscillations In Health Andsupporting
confidence: 58%
See 1 more Smart Citation
“…If reduced early PYRs II/III activity is deleterious, the opposite effect is equally detrimental. Unpublished results from our group suggest, for instance, that a protracted but subtle increase of PYRs II/III firing across the first two postnatal weeks results in long-term prefrontal microcircuit disruption and an excitation/inhibition (E/I) imbalance that worsens over time, equally leading to cognitive and social deficits [43]. Similar deficits have also been described in mouse models of autism spectrum disorder, which are characterized by increased prefrontal activity [54][55][56].…”
Section: Figure 2 Schematic Representation Of the Development Of Beta-gamma Prefrontal Oscillations In Health Andsupporting
confidence: 58%
“…However, recent studies in neonatal mice, conducted with and without anesthesia (Box 3), identified transient bouts of beta-low-gamma rhythmic oscillations as an early prefrontal activity signature with important functional correlates [12,41,42]. This activity is generated by pyramidal neurons residing in supragranular layers of the PFC (PYRs II/III ) [41,43,44], is elicited by light activation of PYRs II/III , and occurs naturally in response to incoming stimuli from the hippocampus [12,45]. Unpublished results from our group suggest that this oscillatory motif persists and evolves smoothly from the first postnatal week throughout adulthood, gradually becoming longer, faster (the average frequency increases from~15 Hz up to~50 Hz), and of higher amplitude [44].…”
Section: Early Patterns Of Electrical Activity In the Pfcmentioning
confidence: 99%
“…We speculate that the extent of the axon reach in the hippocampus might be reduced resulting in each PV+ interneuron inhibiting a different number of postsynaptic cells in the local network, introducing variability in the synchronization of cell assemblies and an overall enhancement in the excitatory tone in the hippocampus (Figure 5 -Figure Supplement 1B). Furthermore, recent work proposed that neuronal entrainment at γ-frequencies during development can impact neuronal morphology of cortical cells (Bitzenhofer et al, 2019). Thus, it will be of great interest to explore the relationship between network activity at γ-frequency and neuronal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, (i) the pCREB-mediated signaling pathway is critically important for survival and morphological maturation of adult-born cells both in the hippocampus and the OB (Herold et al, 2011; Jagasia et al, 2009); (ii) Ca 2+ -dependent CRTC1 signaling is required for dendritic growth of neonatal cortical neurons (Li et al, 2009); and (iii) L-type channel-mediated spontaneous Ca 2+ signaling is critical for migration and survival of neonatal OB GCs (Stéphane et al, 2020). Moreover, modification of cell-intrinsic neuronal activity and associated spontaneous Ca 2+ transients by either overexpression/blockade of different voltage-gated Na + and K + channels or optogenetic stimulation impacts the (iv) migration and/or morphogenesis of neonatal cortical pyramidal cells and interneurons (Bando et al, 2014; Bando et al, 2016; Bitzenhofer et al, 2021; De Marco Garcia et al, 2011; Hurni et al, 2017); and (v) morphogenesis of adult-born hippocampal (Piatti et al, 2011) and OB (Dahlen et al, 2011) GCs as well as (vi) survival of olfactory bulb GCs (Lin et al, 2010). Interestingly, the molecular pathways described above are also very similar to the ones governing the activity-dependent synaptic plasticity as well as spatial memory acquisition and retrieval in the adult brain (Ch’ng et al, 2012; Cohen et al, 2018; Kovacs et al, 2007).…”
Section: Discussionmentioning
confidence: 99%